Individual Values and Person-Organization Fit in faculty members and Staff of the Qom University - Susan Bahrami; Reza Jafariharandi (Allameh Tabataba'i University Press, 2017)
Today, human resources is the strategic source of the organization and an organization has a value system and each of the human resources of the organization also has its own unique value system, organizational proportions refer to people's mental beliefs about the degree of coordination of personal values with organizational culture. The aim of this paper is to determine the multiple relationship between individual values and person-organization fit, faculty members and staff of college faculties. The present study was a descriptive research, multivariate correlation. The statistical population of the research was the total faculty members and staff of the Qom University and stratified random sampling method. The research instruments were standard questionnaires that their validity and reliability were calculated. The results showed that the mean scores of individual values among faculty members were higher than average and in the staff was moderate, the score of person-organization fit between faculty members was moderate and in the staff was lower than average.There is a positive and significant relationship between components of individual values (power, success, benevolence, independence, universalism, conformity, pleasure, arousal, tradition and security) and person-organization fit, there is significant multiple relationship between 4 value styles and person-organization fit.